Gout and ‘Podagra’ in medieval Cambridge, England - Dittmar, Jenna M. (Int J Paleopathol, 2021)
OBJECTIVE: To estimate the prevalence rate of gout and to explore the social factors that contributed to its development in the various sub-populations in medieval Cambridge. MATERIALS: 177 adult individuals from four medieval cemeteries located in and around Cambridge, UK. METHODS: Lesions were assessed macroscopically and radiographically. Elements with lytic lesions were described and imaged using micro-computed tomography (μCT) to determine their morphology. RESULTS: Gout was identified in 3 % of the population. Individuals buried in the friary had highest prevalence (14 %), with low prevalence rates in the Hospital (3 %) and town parish cemetery (2 %), with no cases in the rural parish cemetery. Gout was more prevalent during the 14th–15th centuries than the 10th–13th centuries. CONCLUSION: The high prevalence rate of gout in the friary is at least partly explained by the consumption of alcohol and purine-rich diets by the friars and the wealthy townsfolk. Medieval medical texts from Cambridge show that gout (known as podagra) was sometimes treated with medications made from the root of the autumn crocus. This root contains colchicine, which is a medicine that is still used to treat gout today. SIGNIFICANCE: This is one of the first studies to assess the epidemiology of gout in medieval England and suggests that gout varied with social status. LIMITATIONS: Our sample size precludes statistical analysis. SUGGESTIONS FOR FURTHER RESEARCH: Additional studies that assess the epidemiology of gout in medieval Europe is needed in order to be able to fully contextualize these findings.